STRATEGI PENGEMBANGAN USAHA DENGAN ANALISA SWOT DAN AHP DI UD. MULIA KASIH WOOD - Edy Parman H Sitio; Juarni Juarni (JURUTERA - Jurnal Umum Teknik Terapan, 2018)
Business development strategy is a way of the organization achieves its objectives, according to opportunities and threats faced by the external environment and internal resources and capabilities of an organization. This research aims to explain the internal factors (strength-weakness) and external factors (opportunities-threats) on the business UD. Mulia Kasih Wood, so that the society knows the strategy of development on the business by using SWOT and AHP analysis method. The internal and external factors of business UD. Mulia Kasih Wood's is: From SWOT analysis, internal factor which is strength (Strengths / S) has bigger value than weakness (Weakness / W) is 1.74> 0.66. Then, UD.Mulia Kasih Wood's love has a higher power than the weakness factor to do business development strategy. Then the external factor which is opportunity (Opportunities / O) has bigger value than Threats (T) that is 1.59> 0.61. Thus UD.Mulia Kasih Wood's love has a higher chance compared to the threat factor to do business development strategy From the results of AHP analysis can be concluded that the strategy criteria applied to the development of business UD. Mulia Kasih Wood: Strengths Opportunities is Maximizes strength and opportunity, Strengths Threats is Maximizes power and minimizes threats, Weakness Opportunities is Minimizes weaknesses and maximizes opportunities, Weakness Threath is Minimizes weaknesses and threats.